Meningkatkan Keunggulan Kompetitif Lembaga melalui Strategi Pemasaran Efektif (Studi Kasus RA Masyitoh 32 Pasinggangan) - Ma’mun, Ahmad Aji Jauhari; Ali, Musyafa; Marlina, Marlina (ARZUSIN, 2025)
Raudhatul Athfal Institution occupies a unique position in the community along with the increasing attention and interest of the community in religious educational institutions, but effective marketing strategies have not been widely implemented by many RA institutions. This article examines in more depth the strategy of RA Masyitoh 32 Pasinggangan in marketing its institution. The research approach used is qualitative with the type of case study research, data obtained through interviews, observations and documentation. The results of the study found that 1) RA Masyitoh 3 Pasinggangan formulated market conditions through 3 activities, namely micro-environmental analysis, marketing orientation and competitor analysis, 2) Marketing strategies for competitive advantage used are cost strategy and differentiation strategy. 3) Market segmentation is carried out based on demographics and behavior, Targeting is carried out based on customer orientation and specific market strategy (Single segment concentration) and positioning is carried out with the characteristics of superior Islamic learning program quality. 4) The market mix utilized for market advantage is programs, human resources and effective promotions.